If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2c + -4c = 4 Combine like terms: 2c + -4c = -2c -2c = 4 Solving -2c = 4 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-2'. c = -2 Simplifying c = -2
| (3m+13)= | | -6x-9+8x=4 | | 16+4x=(-32) | | x(12-x)=35 | | t/2=2.5 | | 333+5z=-8(9z-6) | | a/4+3= | | m(5m-17)=12 | | .33(x+6)=0.25x+8 | | 6m+8(m+1)=92 | | 4x+8x=81 | | (-24)=3x-(-9) | | -2x+2=-5x+16 | | x-1=36 | | 7n/5=7 | | -6d=24 | | x-3/15=2/5 | | 5x-5=(-10) | | 3e=9 | | K-12=3k | | 4x^2+39x+90=0 | | 2(b-4)=-2b+8 | | 2x-32=180 | | 14+5n=4+17 | | -2x+2=-5+16 | | 12y^2=5y+3 | | 1.86g-10=0.23 | | 2x+3x+100=180 | | 5(0.45)=1.70 | | -24*4-53=39-4 | | 4b-3-8b-9= | | f=1.8c+32+16 |